NUTRITIONAL HEALTH STATUS WITH DIFFERENT ASPECT OF TARGET GROUP (PREGNANT AND LACTATING WOMEN): A LITERATURE REVIEW - Singh Dhakad, Rajeev; Kumar, Abhishek (International Journal of Research -GRANTHAALAYAH, 2019)
The pregnant women and lactating women are considered as the nutritionally exposed group specifically in the emerging countries. The present paper is mainly focusing on nutritional intake status/behaviours with respect to the culture, beliefs, habits, socioeconomic status and the knowledge and awareness of the target group i.e. pregnant and lactating women. Method: we were review various literature and studies with the keywords such as nutrition, dietary intake, food intake behaviour, culture and practices. In this paper literature were divided it into three sections. These were (a) Nutrient and Dietary Intake; (b) Cultural Beliefs and Practices; (c) Socio-Economic Characteristics. Results: Nutrient and dietary intake were not matched with recommended RDA. Cultures beliefs and practices were very changed in the different community and economic groups such as tribal community were not taking important food during pregnancy and lactation period and Urban women had the higher knowledge of nutrition diet compared to rural women. Socio-economic condition influences the dietary behavior or food’s choice of pregnant and lactating women. Conclusions: Various studies and papers were reviews in this paper, we found gaps between recommended RDA, nutritional behavior, and practices in the target groups of developing countries such as India. This paper concludes the further research and intervention are required on pregnant and lactating women on nutritional behaviour as well as dietary practices.